Creating Masjid Miniature from Ice Cream Sticks: An Islamic STEAM Learning to increase Students Creativity in Pandan Jaya Guidance Studio, Malaysia - Ridha, Zaifatur; Usmaidar, Usmaidar; Alqadri, Muamar; Nurmisdaramayani; Viada, Maya; Nia (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
Activities at the Pandan Jaya guidance studio show that motor skills can positively influence children's creativity. Good motor skills can improve children's cognitive abilities, which ultimately support the development of students at the Pandan Jaya guidance studio and impact cognitive development and improved learning outcomes. This study examines the effectiveness of the Islamic STEAM (Science, Technology, Engineering, Arts, Mathematics) Learning approach in improving students' creativity and motor skills by making miniature mosques from ice cream sticks at the Pandan Jaya Guidance Studio, Malaysia. Creativity and motor skills are two important aspects in children's development that are interrelated and support the learning process holistically. This study uses a descriptive qualitative approach with a participatory method. Data collection techniques include observation, interviews, and documentation of students directly involved in practical activities. The study's findings indicate a strong connection between students' involvement in creative activities and the development of their motor skills. Students who actively participated in art and physical activities were observed to have better body coordination and demonstrated more innovative thinking patterns. The observations also revealed that an interactive and spiritually enriched learning environment enhanced the Islamic STEAM approach's effectiveness in supporting cognitive and non-cognitive development. Based on these findings, this study recommends the integration of Islamic value-based STEAM learning into the children's educational curriculum, both in formal and non-formal settings.